Enhancing international medical graduates' communication: the contribution of applied linguistics. Issue 8 (7th July 2015) - Dahm, Maria R; Yates, Lynda; Ogden, Kathryn; Rooney, Kim; Sheldon, Brooke
<x xml:space="preserve">Abstract</x> Context International medical graduates (IMGs) make up one‐third of the Australian medical workforce. Those from non‐English‐language backgrounds can face cultural and communication barriers, yet linguistic support is variable and medical educators are often required to provide feedback on both medical and communication issues. However, some communication difficulties may be very specific to the experiences of IMGs as second language users. Objectives This interdisciplinary study combines perspectives from applied linguistics experts and clinical educators to address IMGs' difficulties from multiple dimensions and to enhance feedback quality. Methods Five video‐recorded patient encounters with five IMGs were collected at Launceston General Hospital. Three clinical educators gave quantitative and qualitative feedback using the Rating Instrument for Clinical Consulting Skills, and two applied linguistics experts analysed the data for language, pragmatic and communication difficulties. The comparison of the educators' language‐related feedback with linguistic analyses of the same interactions facilitated the exploration of differences in the difficulties identified by the two expert groups. Results Although the clinical educators were able to use their tacit intuitive understanding of communication issues to identify IMG difficulties, they less frequently addressed the underlying issues or suggested specific remedies in their feedback. Conclusions This pilot study illustrates the effectiveness of interdisciplinary collaboration in highlighting the specific discourse features contributing to IMG communication difficulties and thus assists educators in deconstructing their intuitive knowledge. The authors suggest that linguistic insights can therefore improve communications training by assisting educators to provide more targeted feedback.